Molecular evidence of ribosomal DNA (rDNA) amplification of a minichromosome derived from Drosophila arizonae in D. mulleri-D. arizonae hybrid males - Leoncini, Orilio; Tovar, Francisco J.; Bicudo, Hermione E.M.C. [UNESP] (My University, 1996)
We present data supporting cytogenetic observations on nucleolar dominance in hybrids between Drosophila arizonae and D. mulleri. Our approach was to compare the rDNA restriction patterns between the parental species and their hybrids. Results demonstrated that the minichromosome attached to the nucleolus in hybrid males is derived from D. arizonae.
Keywords: ribosome dna; animal experiment; cytogenetics; drosophila; gene amplification; hybrid; male; minichromosome; nonhuman